PREVALENCE OF MALARIA IN BLOOD DONORS IN A TERTIARY CARE HOSPITAL IN PESHAWAR - Jan, Zahish Safiullah; Jan, Nayab Safiullah; Safdar, Humaira; Rehman, Ayesha; Khan, Khizar Abdullah; Humayun, Sidra (Pakistan Journal of Physiology, 2022)
Background: Malaria is a protozoan parasitic infection of humans resulting from one or more of the five species of the genus Plasmodium. A transfusion transmitted infection (TTI) is a virus, parasite, or other potential pathogen that can be transmitted in donated blood through transfusion to a recipient. The aim of this study was to find out the frequency of malaria in blood donors at a tertiary care hospital in Peshawar. Methods: A total of 218 patients were observed in this descriptive cross-sectional investigation from 16 April to 16 October 2021, at Department of Pathology, Hayatabad Medical Complex, Peshawar. Informed consent was obtained from the blood donors justifying the inclusion criteria. Three ml venous blood of each donor was collected in EDTA containing vacutainer. The complete blood count was done on CELL-DYN Ruby® analyzer. Geimsa stained thick and thin blood films were made from each donor blood sample and was examined under ×100 objective lens (oil immersion) using a light microscope for Plasmodium. Results: Mean age of the subjects was 32±11.46 years; 88% donors were male and 12% were female. The frequency of malarial parasite was 4% in blood donors. The transmission of malarial parasite was found significant with a history of fever among the blood donors (p<0.05). Conclusion: The frequency of malarial parasite was 4% in blood donors presenting at a tertiary care hospital of Peshawar, Pakistan. Pak J Physiol 2022;18(3):27?9